Analisis Pembangkit Listrik Tenaga Biogas Berbasis Konsep Green Technology Studi Kasus di Desa Puter Kembangbahu - Nahdia Rupawanti BR; M Iqbal Syauqi (Universitas Islam Lamongan, 2018)
This research is based on the exploration of renewable energy utilization by utilizing the potential of cow livestock waste in cattle farm area as a raw material of biogas energy using the green technology concept. The results of this research show that: (1) the performance of biogas power plant with 115 cattle population producting: 25 kg/day cow waste for each cow in average, 2.857 kg/day cow waste in average for the total population, biogas potency 23 m3/day, methane potency 12,006874 m3/day, total solid 4,83 kg/cow/day, total solid percentage 0,168 %, volatile solid 437 kg/day, and volatile solid percentage 0,152 %, (2) The efficiency of biogas power plant potency of 23 m3/day can be converted into the generated electric energy equal to 1,0005 KWh, 220 W of power flame within 5 hours. Therefore, the power generated from biogas power plant is 1 KWh.